Studies in Comparative Germanic Syntax : Proceedings from the 15th Workshop on Comparative Germanic Syntax - Zwart, C. Jan-Wouter; Abraham, Werner (John Benjamins Pub., 2002)
This volume presents a collection of articles reporting on new research carried out within the theoretical framework of generative grammar on the comparative syntax of the Germanic languages. Divided in four main sections, the book focuses on issues of subordination and complementation (with emphasis on German/Dutch and Danish), displacement phenomena discussed in relation with richness of morphology (with special attention to English, German/Dutch, and Norwegian, as well as presenting more general discussion of the issue), language variation and change (studying historical English syntax and F.
Papers from an international conference held at the University of Groningen, Groningen, Netherlands, May 26-27, 2000.
Keywords: German language -- Syntax -- Congresses.; Germanic languages -- Syntax -- Congresses.; English language -- Syntax -- Congresses.; Allemand (Langue) -- Syntaxe -- Congrès.; Langues germaniques -- Syntaxe -- Congrès.; FOREIGN LANGUAGE STUDY -- German.; English language -- Syntax; German language -- Syntax; Germanic languages -- Syntax; Sprog -- Tysk, nederlandsk sprog.; Conference papers and proceedings